Adaptive Currents: Of Staying, Labour, and the Work of Being With - Xiao, Peng (My University, 2025)
Title: Adaptive Currents: Of Staying, Labour, and the Work of Being With This thesis project explores processes of situated and collaborative practice through the artwork, Where Things Misplaced Persist (2024/25). It was realised as a circulatory, open-ended form dispersed across four encounters: Postcards/Archives, Helsinki 11, Lost & Found, and Shop. Recognising that much of the discourse around such practices has emerged unevenly across cultural contexts, my writing serves as a critical reflection that positions the work in relation to the heterogeneous forms of situational art practice, while also maintaining my own positional context. The project began with my discovery of a small secondhand shop in Kallio, where I spent fifteen months working alongside Jari Tapani, the shopkeeper. My approach entails building a long-term engagement as a mode of learning and staying-with, attuned to the shifting rhythms of the place. Yet, the project was marked by the unforeseen closure of the shop, which unsettled the continuity of our engagement, guiding the emergence of the four registers through which the audiences eventually encountered the work in the context of Kuvan Kevät. This temporal shift necessitated the development of methodologies that remain attentive, situated, and responsive. The research connected to the thesis project explores the visual methodologies employed in the making of the artwork, such as installations and relational practices, while also functioning as a thought experiment that expands the conceptual and temporal scope of the project considered retrospectively. In doing so, the thesis project contributes to discussions of how persistence, companionship, and dispersed forms function as both sites of engagement and reflections on the circulation of labour, material, and meaning, thereby extending understandings of how artistic labour may be constituted today.
Keywords: informal labour; subaltern; persistence; staying-with; companionship; biculturation; situatedness; embeddedness; fugitivity; deskilling and reskilling; topological turn; respatialized art; project turn; futural; dispersed artistic labour; circulatory form; cultural intersectionality; situational practice; relational practice; site-specific art; care; labour culture; diaspora; urban space; artistic research; art; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|